Lymphocyte transformation responses to phytohaemagglutinin and pokeweed mitogen in patients at differing stages of HIV infection: are they worth measuring?. Issue 9 (September 1993) - Bansal, A S; Moran, A; Potter, M; Taylor, R; Haeney, M R; Mandal, B K
Abstract : AIMS–To determine whether the routine measurement of lymphocyte transformation responses to mitogenic stimuli provide any information additional to that available from routine T cell CD4 and CD8 analysis in patients with HIV infection. METHODS–The case records of 197 immunologically investigated HIV seropositive patients were reviewed. The influence of disease stage on T lymphocyte subsets and lymphocyte transformation responses (LyTR) to phytohaemagglutinin (PHA) and Pokeweed mitogen was assessed. RESULTS–The median CD3 and CD4 counts and LyTR to PHA and Pokeweed mitogen were highest in patients with persistent generalised lymphadenopathy (PGL) and decreased progressively in the order: asymptomatic patients, those with ARC, those with AIDS. LyTR to PHA was preserved in over 70% of all patients, but the response to Pokeweed mitogen was depressed in 8% of patients with PGL, 34% of asymptomatic patients, 68% of those with ARC and 78% of those with AIDS. Subnormal values of both CD4 + T cells and LyTR to Pokeweed mitogen were more common in patients with ARC and AIDS (68%) than in those who were asymptomatic or had PGL (20%). CONCLUSIONS–CD4 T cell analysis and LyTR to Pokeweed mitogen, but not to PHA, both correlate with disease states in patients with HIV infection.